Socio-Economic and Cultural Transformation in India: The Impact of Socio-Economic Transformation on Business in India (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The social structure and the culture of society have great influence on the functioning of business activities. Each society has its own culture which consists of the customs, values, attitudes, beliefs, habits, languages and other forms of interaction between the members of the society. Any business firm which aims at entering any market for its products and services must develop complete understanding of socio economic philosophy of the society. In the era of globalisation, no business can survive and grow without social harmony and without understanding the impact of demographic changes in the country or in a region. This paper focuses on the changes in socio-economic environment in India and its impact on business in the future. India opened up its economy in the mid-nineties after a noteworthy emergency of outside trade crunch that dragged the economy near defaulting on advances. The reaction was a huge number of local and outer sector approach measures mostly incited by the prompt needs and somewhat by the request of the multilateral associations. The new monetary approach launched by our present Prime Minister, drastically pushed forward for a more open and market planned economy.